GIT Microbiome and Pharmacology: Implications for drug Metabolism and Therapeutic Outcomes - Al-Yassen, Ahmed M.; Alobaidi, Ibrahim Amer (Journal of Pharmacology and Drug Development, 2025)
Introduction and analysis: A comprehensive literature search was performed using PubMed and Google Scholar databases. The paper analyses works published within 2013 and 2025 were highlighted to ensure up-to-date judgements. Microorganism settle with all human body surfaces like gastrointestinal tract. Affecting broad of aspects regarding body physiological activities as a mediator, homeostasis, metabolism, inflammatory responses and most important is the interaction between gut microbiota enzymes and orally administered drugs. The review discuss many interventions regards microbiota within drugs that leads to hinder and fluctuates the bioavailability and effectiveness. Some interactions lead to reduce the efficacy of intake drugs while other may boost the therapy, by its effect on absorption, metabolism and reconditioning. A list of examples easy to access within database reveals the dug microbiota interaction by different mechanism, this review shows few examples upon different way of interaction to present a clear understands to such interventions. Conclusion: It is worthy to aim targeting the gut microbiota in different diseases, to assist in slow progression and improve the treatment. Therefore, by concentrating on all of these gaps and offering a genuine answer through creative methods, new trustworthy diagnostic tools, and microbiome targeted therapy, it is hoped to reduce response fluctuation and improve quality of life.